PENGEMBANGAN MODUL PEMBELAJARAN KIMIA PADA MATERI SISTEM PERIODIK UNSUR BERBASIS KEARIFAN LOKAL PAPUA PESERTA DIDIK KELAS X SMA NEGERI 4 JAYAPURA - SUBIYANTO, SUBIYANTO; SIREGAR, TIURLINA (Jurnal Ilmu Pendidikan Indonesia, 2018)
This research is a research and development with the aim of knowing how to develop chemistry learning modules in the material of periodic system elements based on Papuan local wisdom students of class X SMA 4 Jayapura. The number of samples in this study 41 students of class X MIPA-4 SMA Negeri 4 Jayapura with representative descriptive data analysis techniques to determine the feasibility of the module. The results showed that: (1) Development of modules with stages of information gathering, planning, development, validation and testing; (2) Feasibility of the learning module compiled, based on the validation of the material validator obtained an average of 91.3% with a very feasible category, the validation of the media validator obtained a mean of 94.75% with a very feasible category while the results of the teacher response 100% strongly agree with the module learners' learning and responses of students with an average of 84.2% with interesting categories (3) This learning module is very useful for students, teachers, schools and government, (4) There is an increase in learning outcomes of class X students by using chemical modules material of periodic system elements based on local wisdom with n-Gain RPP-1 value of 0.59, RPP-2 of 0.60 and RPP-3 of 0.67 with an average n-Gain value of 0.62 medium category, (5) the advantages of learning modules based on Papuan local wisdom are the first module based on local wisdom, easy to understand, contextual Papuans, language is easy to understand and improve learning achievement chemistry. Keywords: Development of learning modules, local Papuan wisdom, elemental periodic system